Balloon-like coupling between head and posterior in a caterpillar. (August 2021) - Okuya, Fuminori; Umedachi, Takuya; Kawahara, Yoshihiro
Investigating the viscoelastic mechanical coupling of a gut between the head and posterior is key to understanding the complicated movements of caterpillars. Caterpillar bodies are like a sac filled with fluid. In this article, we propose a locomotion model in which the head and posterior are connected with a spring and damper system instead of a rod; we refer to this as the "balloon model." The numerical experiments reveal the following benefits. Benefit 1: The model can explain a phenomenon that the posterior moves little behind the head. Our model showed such movement causes efficient movement. Benefit 2: The model can explain inching as crawling. The rod model cannot explain inching because the model cannot change the body length. Our balloon model can change the body length drastically and can locomote faster. Benefit 3: The model does not use the stiff organ. Benefit 4: The model can explain the phenomenon called "environmental skeleton, " which causes the body to contract during the locomotion. The balloon model can change body length and create power between the head and posterior. This model not only simulates the behavior closer to the actual caterpillar but also can explain the caterpillar with a soft element.